Optimisasi rekayasa proses dan validasi parameter pengukuran di stand uji pengeringan biomassa - Agustinus Giai; Mickael Ruben Kaiway; Joni Joni; Agustinus Agustinus; Samuel Siregar; Syilius Rantepulung; Anastasia Sri Werdhani (Universitas Islam Raden Rahmat, Malang, 2025)
This research is motivated by the need for the efficiency of the biomass solid fuel drying process in existing dryer installations. This study aims to optimize the insulation on the primary and secondary sides of the spiral heat exchanger and validate the electrical power on the heater register and the heat flow measured by the system. The approach used was the application of a mixture of 25 ml ISO PUR K 760 and 100 ml ISO-PUR K760 Härter (ISO-ELEKTRA Elektrochemische Fabrik GmbH) and the comparison of thermal and electrical power results calculated using temperature difference data between the inlet and outlet of the heater register without readings in a PC regulator. Experiments were conducted with constant parameters, i.e. target temperature 50°C, fan power level 7, and compressor electricity consumption 541 W. This study proves that after sealing the spiral heat exchanger, there is an increase in energy consumption efficiency. In addition, the approach based on temperature difference in calculating heat power can improve the accuracy in observing energy in the biomass drying system.